Is it worth being socially responsible? - Csapóné Riskó, Tünde; Péntek, Ádám; Wiwczaroski, Troy (Applied Studies in Agribusiness and Commerce, 2016)
Several definitions for corporate social responsibility (CSR) exist and these vary greatly as to the activities it should cover and their motivators. Among the benefits of CSR are positive marketing/brand building, brand insurance and employee loyalty. Numerous arguments against CSR prevail, e.g. social responsibility is not a problem that belongs in the sphere of activities a corporation should be addressing or even that CSR distracts businesses from addressing the primary need to concentrate on sales. Thus, the strong economic question: is CSR worth it? In 2014, we carried out a representative survey in Hungary, in which the effects of responsible business practices on consumer purchase behaviour were studied. With our research results, we could show that there is a considerable gap between the apparent interest of consumers in CSR and the limited role of CSR in purchase behaviour.JEL classification:M104